Strategi Pemasaran yang Efektif untuk Meningkatkan Pertumbuhan Bank Muamalat Indonesia Studi Kasus Bank Muamalat KCP Batu - Mubaroq, Wildan Syahrun; Hariyanti, Peni (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
This research aims to analyze effective marketing strategies in increasing the growth of Bank Muamalat Indonesia, with a focus on the Batu Sub-Branch Office. The method used in this research is a qualitative method, with a case study approach. Based on the research results, it was found that manual or head-to-head marketing strategies were more effective than digital marketing methods at Sub-Branch Office Batu. The head-to-head approach provides direct interaction between the marketing team and customers, allowing for more personalized and in-depth offers. This strategy has been proven to increase the closing rate of sales significantly, especially for low cost funding and bancassurance products. Factors such as market targeting, product diversification, customer education, and excellent service are the keys to the success of this strategy. In conclusion, implementing a manual marketing strategy really supports the growth of Bank Muamalat Sub-Branch Office Batu with a focus on achieving a higher closing rate